Civil Service Capacity Development: A Case Study of the Regional Civil Service Agency of Banten Province - Maulana, Guslal Achdi; Raharjo, Santoso Tri; Irfan, Maulana (International Journal of Science and Society, 2025)
This study examines strategies for strengthening the capacity of Indonesia’s civil servants (Aparatur Sipil Negara, ASN) through a case study of the Regional Civil Service Agency (BKD) of Banten Province, using Skidmore’s (1995) Staff Processing Model as an analytical framework. Employing a qualitative case study design, data were collected through in-depth interviews, participant observations, and document analysis, and analyzed using Miles and Huberman’s interactive method. Findings show that BKD Banten applies capacity development strategies across Skidmore’s seven core components: recruitment, selection, placement and orientation, formal training, continuing professional development, evaluation and performance appraisal, and promotion, transition, and retention. Beyond these, the study identifies complementary strategies, including the digitalization of personnel management (e.g., e-Kinerja and SIMPEG), the adoption of talent management systems, fostering a culture of lifelong learning, providing psychosocial support during career transitions, and implementing recognition and retention programs for innovative staff. The study concludes that ASN capacity development is not merely an administrative procedure but a dynamic, evolving ecosystem that integrates policy, technology, and organizational culture. These findings expand Skidmore’s model by incorporating digital governance and psychosocial insights, offering both theoretical contributions and practical recommendations for designing merit-based and sustainable civil service reforms.